2014
DOI: 10.1007/s40596-014-0185-9
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Simulation to Teach Suicide Risk Assessment to Health Profession Trainees—Rationale, Methodology, and a Proof of Concept Demonstration with a Virtual Patient

Abstract: Our study provides proof of concept that both VP and video module approaches are feasible for teaching students to assess suicide risk, and we present evidence about the role of active learning to improve communication skills. Depending on the learning context, interviewing a VP or observation of a videotaped interview can enhance the students' suicide risk assessment proficiency in an interview with a standardized patient. An interactive VP is a plausible modality to deliver basic concepts of suicide risk ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 37 publications
0
69
0
Order By: Relevance
“…We are aware that much of the appraisal given was in fact addressed to the video-recorded human actor who role-played the virtual patient. It remains an interesting research question to what degree this effect could be repeated with a computer-generated virtual character [22]. Virtual characters, as elements of user interface, are applied in a growing number of e-learning tools as being more flexible, but are so far of limited expressiveness and are not preferred by students [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware that much of the appraisal given was in fact addressed to the video-recorded human actor who role-played the virtual patient. It remains an interesting research question to what degree this effect could be repeated with a computer-generated virtual character [22]. Virtual characters, as elements of user interface, are applied in a growing number of e-learning tools as being more flexible, but are so far of limited expressiveness and are not preferred by students [22].…”
Section: Discussionmentioning
confidence: 99%
“…It remains an interesting research question to what degree this effect could be repeated with a computer-generated virtual character [22]. Virtual characters, as elements of user interface, are applied in a growing number of e-learning tools as being more flexible, but are so far of limited expressiveness and are not preferred by students [22]. Requests for improvements varied, but the most common was to have more exercises with virtual patients and to create virtual patients with more varied backgrounds and problems.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, early work by Johnsen et al (2007) showed a significant correlation between medical students' performance with a virtual and a human patient, and showed that medical students were able to elicit the same information from the real and virtual human (although showing less interest and poorer attitude toward the latter). More recently, virtual patients have been used in training for mental health assessment (Foster et al, 2015;Washburn et al, 2016), empathetic communication (Kleinsmith et al, 2015), and identifying gender bias in diagnosis (Rivera-gutierrez et al, 2014). In these studies, typically, human participants interacted with virtual patients via text or voice, and the virtual patients were animated and programmed to react toward the participants in a realistic way.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that VPs can successfully facilitate learners' acquisition of core knowledge in psychiatry and help develop their skills in history taking, interviewing, clinical reasoning, decision making, and assessing suicide risk. 8,9 We use psychiatric intake as an example because psychiatric issues such as opioid overuse, posttraumatic stress syndrome, and suicidality are pervasive. Shortages of mental health professionals and services limit learners' exposure to these clinical problems, 10 so VPs could play an especially useful role.…”
mentioning
confidence: 99%
“…Research suggests that VPs can successfully facilitate learners' acquisition of core knowledge in psychiatry and help develop their skills in history taking, interviewing, clinical reasoning, decision making, and assessing suicide risk. 8,9 The Peril of VPs VPs have proven useful, but they have shortcomings. Current VPs might not represent the diversity of a population and, when racial or ethnic diversity is represented, VPs with darker skin tone could trigger learners' unconscious bias.…”
mentioning
confidence: 99%